Determination of Economic Nitrogen Rate for Transplanted Aus Rice Varieties of Bangladesh (Bangladesh Agronomy Journal, 2023)
A field experiment was conducted at the Agronomy field, Bangladesh Rice Research Institute, Gazipur, Dhaka, from April to September 2019 to determine the economic nitrogen rates for popular transplanted Aus varieties. The experiment was carried out in a randomized complete block design (RCBD), with two factors. Factor A: three varieties as- BR26, BRRI dhan48, and BRRI dhan82; and Factor B: five levels of nitrogen rates as- 0, 40, 60, 80, 100 kg ha−1. The experimental data show the individual effect of variety and nitrogen (N) rate was significant in the case of N concentration, N uptake in grain and straw, and nitrogen harvest index (NHI). Overall, increasing N rate increases grain and straw's concentration irrespective of varieties. But higher N concentration and uptake were observed in the N rate of N60-N100 kg ha−1 in all varieties. Among the varieties, BRRI dhan82 observed higher N uptake (61.23 kg ha−1) in grain. Higher total N uptake was also observed in BRRI dhan48 at 80 kg N ha−1. NHI ranged from 55 to 72 % in different N levels, indicating 55 to 72% of the absorbed N translocated to the grains, and 45% to 32% remained in the dry matter within varieties. The estimated economic nitrogen dose for maximum yield was determined by regression analysis, and found that N rates of BR26, BRRI dhan48, and BRRI dhan82 were 97, 95, and 55 kg ha−1, respectively. The findings of this study indicated that the response of different N rates on three Aus varieties was linear up to 80 kg N ha−1 might be owing to better N uptake that made yield increase after that decreasing.Bangladesh Agron. J. 2023, 26(1): 84-95